2020
DOI: 10.1177/0300060520931609
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxidation of low-density lipids in pathogenesis of osteoarthritis: A narrative review

Abstract: Osteoarthritis (OA) is a chronic joint disorder that causes degeneration of cartilage, synovial inflammation, and formation of osteophytes. Aging, obesity, and sex are considered the main risk factors of OA. Recent studies have suggested that metabolic syndrome (MetS) disorders, such as hypertension, hyperlipidemia, diabetes mellitus, and obesity, may be involved in the pathogenesis and progression of OA. MetS disorders are common diseases that also result in atherosclerosis. Researchers believe that OA and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 92 publications
(117 reference statements)
0
20
0
2
Order By: Relevance
“…In addition to iron overload, a large amount of unsaturated lipids also exerts a ferroptotic effect. High lipid levels translate to high ROS and other radical levels, which activate NF-κB signaling pathways and induce inflammation [ 106 ]. Collectively, these results suggest that obese people are more likely to experience collar destruction resulting from fatty oxide exposure and ferroptosis.…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to iron overload, a large amount of unsaturated lipids also exerts a ferroptotic effect. High lipid levels translate to high ROS and other radical levels, which activate NF-κB signaling pathways and induce inflammation [ 106 ]. Collectively, these results suggest that obese people are more likely to experience collar destruction resulting from fatty oxide exposure and ferroptosis.…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
“…Obesity is no longer the sole burden of obese patients but has gradually become the burden of the whole society [ 107 ]. Fatty acids and cholesterol are could be stressful environments, and the cytokines produced by fat cells exert numerous inflammatory effects that often exacerbate other underlying conditions [ 106 ]. In summary, previous studies have investigated the potential relationship between lipid or cholesterol metabolism and bone metabolism at the cellular level.…”
Section: Discussion and Future Prospectsmentioning
confidence: 99%
“…8 OxLDL is involved in the formation of atherosclerotic plaques, and a known regulator of cartilage degeneration via induction of chondrocyte cell death. 13 PLA2G2A, member of the phospholipase A2 family (PLA2), is the membrane-bound form of phospholipase A2, a lipolytic enzyme that catalyses the hydrolysis of membrane phospholipids. 9 Several phospholipase A2 isoforms have been implicated in the pathogenesis of OA via regulation of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, evidence been accumulating that ox-LDL is important in the pathogenesis of osteoarthritis, another common joint disease that often requires surgical treatment [ 44 ]. It was reported that ox-LDL accumulated in chondrocytes in the pathological process of osteoarthritis and that LOX-1-deficient mice were resistant to osteoarthritis induced by instability or age [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%